Diseño de un robot social para el apoyo a terapias con niños con Tea: aplicación del diseño participativo integrando la comunidad en el proceso de ingeniería. (2019)
There is a great variety of pathologies in Latin America susceptible to rehabilitacion, more and more strategies are being explored to maintain and rehabilitate the functional capacity of certain structures. Autistic spectrum disorder (ASD) is a neurobiological disorder that develops during the first years of life and lasts throughout the lives of those who are diagnosed, patients with ASD have deficiencies in the following areas: attacks on social interaction, communication and repetitive behaviors. However, early detection, adequate stimulation combined with knowledge of the health areas, methodologies and innovative tools will allow the patient with ASD to be more autonomous and participatory in society. In the developing countries such as Colombia, the health system has notable limitations in the detection and treatment of ASD, while in developed countries promising results have been obtained with social robots in the treatment of ASD, however, in developing countries import and maintenance costs make unfeasible the implementation of this technology. In this context, the CASTOR project, (CompliAnt SofT Robotics) funded by the “Industry Academy Partnership Program - 17/18” program of the Royal Academy of Engineering of the United Kingdom, aims to develop robotic technologies compatible with the reality of therapeutic scenarios with children with ASD in Colombia, combining the experience of the Colombian School of Engineering and the University of Plymouth, with the support of two companies: Tejidos de Sueños (Medellín) and Fieldwork Robotics (UK). The current document is focused on the design, validation and first treaties with children and their environment in the context of the CASTOR project. The platform is located for children between the ages of two and three years who are diagnosed with ASD, is implementing a participatory methodology for the design of the physical characterization of the robot, this process is in the selection stage of the final design that is represented by means of a sketch that will give the physical appearance to the robot. Initially, a survey was conducted with the therapists at the Howard G. a) clinic during the session. For the selection of the sketch, activities have been carried out in the clinic with parents, therapists and children, through focus groups and surveys, the activities are determined according to each participant. The selection started with 61 sketches and in the first stage it was reduced to 44, later with an online survey it was reduced to 9 sketches and currently there are still three sketches, with these sketches a 3D model was made for the final stage. Positive results were achieved from the activities carried out, along with the acceptance and integration of the community in the participatory design. As a specific result of the 4 design, parents and therapists prefer a human aspect to the robot, while children prefer a futuristic robot appearance or a fantastic character, to minimize this difference it has been thought to design additional objects (caps , costumes, glasses, among others) with the aim of making the robot to the liking of therapists, parents and children.